Microhimenopteros(Insecta : Hymenoptera) parasitoides e insetos predadores de moscas sinantropicas (Insecta : Diptera na Granja Capuavinha, Monte Mor, SP - Monteiro, Marisa Rossi (1995)
Orientador: Angelo Pires do Prado